Staging Desire : Queer Readings of American Theater History - Schanke, Robert A., 1940-; Marra, Kim, 1957- (Book collections on Project MUSE., 2002)
Critical and biographical essays on notable stage personalities who made their mark before 1969, when the Stonewall riots accelerated the lesbian and gay rights movement in the United States. How they staged their unconventional sexualities greatly influenced the course of their personal and professional lives, and thus the course of American theater history.